Stakeholder participatory design and development of an Agri-Infotech portal - A. Sakeer Husain; P. Ahamed; K.M. Nithin (Journal of Agricultural Extension Management, 2017)
The Agri-lnfotech Portal (www.celkau.in), developed by Centre for e-learning of Kerala Agricultural University (KA U) is an JCT enabled bi-lingual platform for demand-driven technology information and advisory services in the agrifront, covering agriculture, animal husbandry, fisheries and allied aspects. It also acts as a platform for online course management in agriculture. As on August 2016, the portal had nearly 16 lakh hits within four years, which show a geometric progression. Besides, the portal won two international awards, one national award and the Kerala Governments e-governance award. This paper analyses the methodology followed for designing and developing this high-end utility web portal. To accomplish this, a basic research mode work on user-centred design, testing, refining and launching of the portal was adopted, as it would match the priorities of its end-users. The utility was ensured by testing and fine-tuning from its designing stage itself. Creating a working model (prototype) before developing the actual portal was the first stage. To generate content, the information needs of the users were identified and prioritized through questionnaires, brainstorming sessions, and focus group discussions. Interpretations based on the priorities, suggestions from the users, and desktop analyses of various similar portals across the world, led to designing of the first prototype. This prototype was subjected to a process of criteria/trait based evaluation by the end-users for further refinement leading to the second prototype. This second prototype was demonstrated before various categories of end-users and stake holders for final fine-tuning